KEANEKARAGAMAN LICHEN SEBAGAI BIOMONITORING KUALITAS HUTAN DI LERENG SELATAN GUNUNG MERAPI YOGYAKARTA - Miftahul Jannah (Scripta Biologica, 2018)
Lichen is an symbiotic organism between algae (Photobiont) and Fungi (Mycobiont). Eruption of Merapi vulcano can be affected lichen diversity. In this research involved a method of descriptive explorative and the aim of this research is to study the diversity of lichen, its character, its distribution and its secondary metabolite in the forest of Turgo dan Kaliurang. Sampling used cruise method. This research based on morphological, chemical test, and Pb and S of metal test. The research was conducted from April to November 2017. The result of research was found three family, there are is Parmeliaceae, Physciaceae, and Lobariaceae. The result of research in Turgo forest found 4 species, there are is Usnea bismolliuscula, U. baileyi, Parmelia sp., and Parmelia crinita, in Kaliurang forest was found 4 species, there are is Parmelia crinita, Parmelia perlata, Physcia sp. and Lobaria amplissima. The result of metal test in Parmelia perlata and Lobaria amplissima was detected sulfur and undetected of Pb metal. The forest of Turgo and Kaliurang was included healthy forest.  Lichen is recommended as healthy bioindicator and biomonitoring in forest.